Efficient degradation of 2, 4-dichlorophenol in aqueous solution by peroxymonosulfate activated with magnetic spinel FeCo2O4 nanoparticles. (April 2018) - Zhou, Rui; Zhao, Jian; Shen, Ningfei; Ma, Taigang; Su, Yu; Ren, Hejun
Abstract: Magnetic spinel FeCo2 O4 nanoparticles (NPs) were synthesized and proposed as a catalyst of peroxymonosulfate (PMS) for the degradation of 2, 4-dichlorophenol (2, 4-DCP). The catalyst was characterized by XRD, TEM, XPS, nitrogen adsorption–desorption isotherms, and magnetization curve. In addition, the effects of parameters, such as initial pH, PMS dosage, FeCo2 O4 addition, and initial concentration of 2, 4-DCP were studied. The results showed that FeCo2 O4 NPs exhibit good properties for the degradation and mineralization of 2, 4-DCP, achieving 95.8% and 44.7% removal of 2, 4-DCP and TOC, respectively, within 90 min under reaction conditions of 4 mM PMS, 0.06 g L −1 FeCo2 O4, 100 mg L −1 2, 4-DCP, pH = 7.0, and T = 30 °C. Furthermore, SO4 − and HO were main radical species in the reaction system was explored. The 2, 4-DCP degradation efficiency could reach 91.8% even after FeCo2 O4 NPs were used for the fifth run. Moreover, the degradation efficiencies of metronidazole (MNZ), methylene blue (MB), and rhodamine B (RhB) could reach 74.8%, 86.7%, and 96.1% under the same reaction conditions, respectively. Results revealed that the FeCo2 O4 /PMS system shows potential for degrading contaminants in the environment. Highlights: FeCo2 O4 NPs can strongly catalyze PMS to degrade 2, 4-DCP at neutral pH. Both SO4 − and HO were identified responsible for 2, 4-DCP degradation. The FeCo2 O4 /PMS system exhibited good degradation ability and general applicability for organic contaminants.